2021
DOI: 10.1097/nna.0000000000001031
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive Study of Resiliency and Health in Practicing Nurses

Abstract: The institutional review board (IRB) of the University of Southern Indiana (USI) provided the certificate of approval for the study (ref. no. 2019-005-NH, December 3, 2018, which was shared with all participating organizations. Some organizations accepted the USI IRB approval for the respective organization, whereas others required IRB approval through their respective board.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Detailed information of the 2 assessment tools have been described in a previous published study. 11…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Detailed information of the 2 assessment tools have been described in a previous published study. 11…”
Section: Methodsmentioning
confidence: 99%
“…The team used the Connor-Davidson Resilience Scale 12 and the PROMIS Global Health scale 13 to measure respondents' resilience level, and physical and mental health status, respectively. Detailed information of the 2 assessment tools have been described in a previous published study 11 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Another study among nurses during the pandemic revealed the need for nurse leaders to support clinical nurse resilience by adopting transformational leadership-style strategies such as encouraging nurses to care for themselves and providing a safe space for effective dialogue. 22 Despite the integral role that frontline nurse leaders play during COVID-19, 16 additional research is needed regarding streamlining the disaster relief pipeline and more efficiently managing disaster preparedness. 23 Given the need to understand nursing leadership and the experiences of nurse leaders during the emergence of the COVID-19 pandemic, [24][25][26] the purpose of this qualitative study was to describe the experiences of self-identified nurse leaders during the 1st wave of the COVID-19 in the United States.…”
mentioning
confidence: 99%